PENERAPAN MODEL PEMBELAJARAN PJBL BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI DAN KEAKTIFAN PESERTA DIDIK: PENERAPAN MODEL PEMBELAJARAN PJBL BERBANTUAN GEOGEBRA - Szalsa Widya Rahim; M. Ridlo Yuwono Ridlo; M. Wahid Syaifuddin Syaifuddin (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
Project Based Learning learning model, a learning model in the form of a project to be carried out individually or in groups and carried out within a certain period of time. The application of the PjBL learning model assisted by the GeoGebra application aims to improve students' numeracy literacy skills and students' activeness, so that students are expected to have curiosity and be able to understand quadratic function material well. This study used the class action research method (PTK) by taking research subjects class X G students of SMA N 1 Jatinom consisting of 36 students. Based on this research, it was shown that students' numeracy literacy skills experienced an increase seen from the classical average in cycle I of 51.88% increasing to 73.97% in cycle II. Meanwhile, the activeness of students began to increase as seen from the average percentage of students' activeness of 57.29% in cycle I and 72.06% in cycle II. It was concluded that in this study the application of the GeoGebra-assisted PjBL learning model in mathematics learning was able to improve the numeracy literacy skills and the activeness of class X G students of SMA N 1 Jatinom in the 2022/2023 academic year.